STMN1–IGFBP5 axis induces senescence and extracellular matrix degradation in nucleus pulposus cells: In vivo and in vitro insights - Lei Li; Guangzhi Zhang; Zhili Yang; Zhenyu Cao; Dongxin Wang; Xuewen Kang (Molecular Medicine)
Abstract Cellular dysfunction induced by senescent nucleus pulposus (NP) cells is a key factor in the pathogenesis of intervertebral disc degeneration (IDD). Stathmin 1 (STMN1) has been proposed as a telomere-associated senescence marker implicated in senescence in many age-related diseases. Nevertheless, its role in NP cell senescence remains unclear. This study revealed that STMN1 was significantly upregulated in human degenerative and naturally aged rat NP tissue specimens. In vitro models demonstrated that STMN1 expression levels were elevated in replicative and TNF-α-induced NP senescence models. Lentiviral knockdown of STMN1 inhibited NP cell senescence, while overexpression promoted NP cell senescence, along with extracellular matrix (ECM) degradation. An in-depth mechanism indicated that insulin-like growth factor-binding protein 5 (IGFBP5), a downstream pro-senescence gene of STMN1, can induce NP cellular senescence and ECM degradation following its upregulation by STMN1. Furthermore, STMN1 knockdown reduced IGFBP5 expression and mitigated IDD development in a rat model of caudal discs puncture-induced IDD. Combined with the abovementioned results, we demonstrated for the first time that the STMN1–IGFBP5 axis can induce NP cell senescence and ECM degradation, thereby accelerating IDD development. This provides a robust foundation for the development of molecular-targeted therapies for IDD.